Public and Patient Involvement and the Right to Health: Reflections from England - Stuttaford, Maria Clasina; Boulle, Therese; Haricharan, Hanne Jensen; Sofayiya, Zingisa (Frontiers in Sociology, 2017)
In this paper we reflect on public and patient involvement (PPI), the right to health and how human rights principles provide values for implementing mechanisms of participation and accountability. Globally, new models of formalized participation, imposed top-down by State institutions, have emerged in recent health system reforms. There is an on-going challenge to ensure that the prescribed mechanisms, or procedural rights, for implementing the substantive right to heath influence social accountability. Participation is linked to procedural rights e.g. through the right to information and fair decision-making processes .We explore recent examples from England to illustrate the challenges posed by formalized participation. Inquiries into health care failures have found participatory mechanisms to be in place but evidence and data collected through formalized participation often ignored. Complaints procedures have not been sufficiently robust to hold duty bearers to account. The examples expose how weak formalized participation and weak accountability have only come to light through civil society-led participation. It is argued that by embracing participation not merely as a mechanism but also as part of a set of values linked to the right to health, formalized participation could be strengthened. Data, evidence and knowledge gathered through formalized participation and civil society-led participation should be valorized alongside other forms of evidence. The indivisibility of the right to health should be recognized through participation across sectors. Adopting PPI as comprising mechanisms and values poses renewed challenges to those with obligations of service provision and to public participants to integrate diverse forms of participation and knowledge that contributes to social accountability.